Estudo dos parâmetros químicos e físico-químicos da semente da Morinda Citrifolia Linn (Noni) - Andrade Neto, Renato Sampaio (2016)
Morinda citrifolia Linn (noni) is an Asian fruit, which was introduced to Brazil by tourists from the Caribbean and Polynesia. Due its adaptation to Brazilian climate, the cultivation was established al ober the country and more proficallyin in the states of Acre, Ceará, Sergipe and São Paulo. With great market value, its cultivation became a profitable activity. Being an exotic fruit with small amount of information about it, research has been done in order to know more about its chemical, nutritional and biological composition. In order to obtain more information about the fruit seeds from the city of Fortaleza-CE, experiments were carried out with fruit seeds harvested in the Garden of medicinal, aromatic and condiment plants of Embrapa Agoindústria Tropical (Fortaleza-CE). It was determined in the seed: The pH, acidity, water activity, lipids, proteins, carbohydrates, ashes and moisture were determined in addition to the concentration of macro nutrients, calcium, phosphorus, magnesium, potassium and sodium, and micronutrients, copper, iron, manganese And zinc by the methods of absorption and atomic emission. The results showed that the seeds has acid characteristics, rich in carbohydrates, with low amounts of proteins and lipids, 5,24% and 6,53% respectively. The low moisture (9.24%) and water activity (0.57) give the noni seed good characteristics for its storage. The amount of ash (0.95%) showed the richness in mineral elements, being an alimentar option for minerals supplies.